2015
DOI: 10.1074/jbc.m114.612705
|View full text |Cite
|
Sign up to set email alerts
|

Processing by Convertases Is Required for Glypican-3-induced Inhibition of Hedgehog Signaling

Abstract: Background: Glypican-3 (GPC3) is a proteoglycan that is cleaved by convertases and that inhibits Hedgehog signaling. Results: Convertase-resistant GPC3 stimulates Hedgehog signaling, and unlike wild-type GPC3, binds to Patched through its heparan sulfate chains. Conclusion: Convertase cleavage is required for GPC3-induced inhibition of Hedgehog signaling. Significance: The structure of the GPC3 core-protein determines the binding properties of heparan sulfate chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
(44 reference statements)
2
26
0
Order By: Relevance
“…Moreover, purified glypican-3 binds with high affinity to Indian and Sonic Hh as well as it competes with Patched for Hh binding [ 83 , 89 ]. A recent study has shown that processing by convertases is required for GPC3-evoked suppression of Hh signaling, and this process is dependent on the HS chains and their degree of sulfation [ 90 ]. Thus, the glypican family is not only complex in nature, but is also the control of various modifying enzymes (proteases and lipases) that modulate its biological activity.…”
Section: Cell Surface Proteoglycansmentioning
confidence: 99%
“…Moreover, purified glypican-3 binds with high affinity to Indian and Sonic Hh as well as it competes with Patched for Hh binding [ 83 , 89 ]. A recent study has shown that processing by convertases is required for GPC3-evoked suppression of Hh signaling, and this process is dependent on the HS chains and their degree of sulfation [ 90 ]. Thus, the glypican family is not only complex in nature, but is also the control of various modifying enzymes (proteases and lipases) that modulate its biological activity.…”
Section: Cell Surface Proteoglycansmentioning
confidence: 99%
“…Of note, the core protein of GPC3 can directly bind Hh to inhibit its signaling activity in cell culture (26). In a later study, experimental evidence demonstrated that cleavage by convertases is also crucial for GPC3 inhibition of Hh signaling (56). Low-density-lipoprotein receptor-related protein-1 (LRP1) was also shown to mediate endocytosis of the GPC3-Hh complex (57) (Figure 2B).…”
Section: Gpc3 Wnt and Hedgehog Signalingmentioning
confidence: 99%
“…Furthermore, levels of GPC3 in blood differ across reports, with values ranging from several pg/ml to several µg/ml (12,15,(19)(20)(21)(22). Although the roles of GPC3 and its physiological significance have not yet been elucidated, it is thought to relate to the regulation of cell differentiation and proliferation and to exert these functions only after being cleaved and configured into the full-length form by the disulfide bond between N-and C-terminal domains (13,23).…”
Section: Introductionmentioning
confidence: 99%